An efficient anonymous authentication and key agreement scheme with privacy-preserving for smart cities. (June 2021) - Xia, Xueya; Ji, Sai; Vijayakumar, Pandi; Shen, Jian; Rodrigues, Joel J. P. C.
Internet of Things devices are responsible for collecting and transmitting data in smart cities, assisting smart cities to release greater potential. As Internet of Things devices are increasingly connected to smart cities, security and privacy have gradually become important issues. Recently, research works on mitigating security challenges of Internet of Things devices in smart cities mainly focused on authentication. However, in most of the existing authentication protocols, the trustworthiness evaluation of Internet of Things devices in smart cities is ignored. Considering the trustworthiness evaluation of Internet of Things devices is an important constituent of data source authentication, in this article, a cloud-aided trustworthiness evaluation mechanism is first designed to improve the credibility of the Internet of Things devices in smart cities. Furthermore, aiming at the problem that the user's privacy is easy to leak in the process of authentication, an anonymous authentication and key agreement scheme based on non-interactive zero knowledge argument is proposed. The proposed scheme can ensure the privacy preservation and data security of Internet of Things devices in smart cities. The security analysis demonstrates that the proposed scheme is secure under q-SDH problem. The experimental simulation indicates that the performance of the proposal is greatly improved compared with other similar schemes.